Pengenalan Pencatatan Akuntansi pada UMKM Sebagai Pengetahuan dalam Pengembangan Usaha Penyewaan Kamar dan Otomotif di Desa Pasirangin - Dhini Ramadhanty; Martinus Budiantara (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article aims to discuss the introduction of accounting records in Micro, Small, and Medium Enterprises (MSMEs/ UMKM) as knowledge in developing room and automotive rental businesses in Pasirangin Village. This research uses a field study method with observation and training techniques. After conducting research, it can be concluded that MSMEs are businesses that can encourage the economic development of society. Many methods are offered in developing MSMEs, such as digitalization. However, the results of observations in the field, turned out that to develop potential and maintain the business that has been carried out, training needs to be held to maintain the quality and quantity of production produced by MSMEs. If MSMEs players receive training to develop their capabilities adequately, the MSMEs market can be optimized as a source of community economic needs that is more practical and easier to implement, especially developing room and automotive rental businesses in Pasirangin Village.